The wrong road taken: Social media content, self-authentication and misapplication of the business records rule / Fatin Atirah Siman - Siman, Fatin Atirah (Perpustakaan Tun Abdul Razak, Universiti Teknologi MARA Sarawak, 2022)
The reason why we choose this article is because this article shows a few set of rules of handling the business records in the social media. The article also explained on what contents that will violates the use of social media. Self-authentication and misapplication of business records rule were also mentioned in the article. It is also to show the truth of some contents in the social media.